Inheritance of induced morphological mutants in triticum-monococcum l - Multani, Dilbag S.; Sharma, S.K.; Dhaliwal, H.S.; Gill, Khem S. (Wiley, 1992)
The mode of inheritance of fifteen induced morphological mutants in diploid wheat Triticum monococcum L. was determined. The results showed that earliness, reduced height, uniculm, liguleless branched spike, compact ear, and free‐threshing habit of each of these mutants is the result of a single recessive mutation. Red awns and xantha traits are controlled by two recessive genes with duplicate and inhibitory gene interactions, respectively. Some of the early and dwarf mutants were non‐allelic. One dwarf GA3‐insensitive mutant with recessive gene action may be a new source. Mutants such as early maturing, dwarf and free threshing habit may be of significance in breeding diploid wheat.